DEVELOPING LISTENING MATERIALS IN 21ST CENTURY: STUDENTS’ VOICES OF NEEDS, LACKS, AND WANTS IN SMPN 5 JEPARA - Andra Andriawan; Ainan Salsabilla; Santi Andriyani (E-LINK JOURNAL, 2022)
This research is the initial stage in research on the development of teaching materials where researchers try to find out the needs of learning English in class IX students of SMP N 5 Jepara in the 2020/2021 academic year. The researcher used a qualitative and quantitative descriptive research design. Researchers used test and non-test instruments. The instruments consist of listening tests and questionnaires. The respondents were students of class IX SMP N 5 Jepara. Then, the data analysis used is the Miles and Huberman method which consists of data reduction, data display, and verification. The results obtained from the analysis of the needs for learning English for class IX at SMP N 5 Jepara are: 1) the completeness of listening material are still low. 2) the listening pre-test indicates that students' listening skills are still lacking. 3) the interview with the teacher shows that teacher had difficulty in finding listening material.Keywords: Need Analysis, English Materials, Listening